Development of low-Si aluminum casting alloys with an improved thermal conductivity - Shin, Jesik (Materiali in tehnologije, 2014)
To develop an aluminum alloy that can combine a high thermal conductivity witha good castability and anodizability, low Si-containing aluminum alloys, Al-(0.5-1.5)Mg-1Fe-0.5Si and Al-(1.0-1.5)Si-1Fe-1Zn alloys were assessed as potential candidates. The developed alloys exhibited a thermal conductivity of 170-190 % level (160-180 W/(m K)), a fluidity of 60-85 % level, and an equalor higher ultimate tensile strength compared to those of an ADC12 alloy. In each developed alloy system, the thermal conductivity and the strength decreased and increased, respectively, as the content of the major alloying elements, Mg and Si, increased. The fluidity was inversely proportional to the Mg content and directly proportional to the Si content. The Al-(1.0-1.5)Si-1Fe-1Zn alloys showed better thin-wall castability due to their lower surface energy. In the experimental aluminum alloys with a low Si content, the fluidity was mainly dependent on the melt surface energy, the Al dendrite coherency point (DCP), and the first intermetallic crystallization point (FICP), rather than on the solidification interval, latent heat, or the viscosity.
Keywords: aluminijeve zlitine; aluminium alloy; aluminum alloys; oblikovanje zlitine; alloy design; thermal conductivity; toplotna prevodnost; castability; livna sposobnost